1953
DOI: 10.1017/s002531540001153x
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Asterias rubens L.V. A Porphyrin pigment in the integument

Abstract: A porphyrin was extracted by MacMunn (1886), working at Plymouth, from the integument of Asterias rubens then known as Uraster rubens. He extracted whole starfishes with ethanol and ammonia and also with ethanol and sulphuric acid. After diluting his acid-ethanol solution with water he shook the extract with chloroform; the chloroform solution showed two absorption bands, at 607-593 and 566-548 mfl-. On evaporation this extract yielded a brown amorphous residue which he found to be soluble in absolute ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1955
1955
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Sciurus niger has black hair, so that in these two widely differing animals an additional pigment is present, namely melanin, which protects these animals from the photosensitizing effects of the porphyrin. Aplysia and Akera which are more darkly co10ured, have more uroporphyrin I than Duvaucelia which has a bright orange pigment; there was a much greater concentration of coproporphyrin III in the body wall of the dark co10ured Arenicola and Amphitrite than in the lighter, pink specimens: the more darkly pigmented Asterias contained more protoporphyrin IX than the paler animals (Kennedy & Vevers, 1953) although protoporphyrin is not noteworthy for its photosensitizing action. Fischer & Zerweck (1924) have shown in mammals that photosensitivity to u.v.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Sciurus niger has black hair, so that in these two widely differing animals an additional pigment is present, namely melanin, which protects these animals from the photosensitizing effects of the porphyrin. Aplysia and Akera which are more darkly co10ured, have more uroporphyrin I than Duvaucelia which has a bright orange pigment; there was a much greater concentration of coproporphyrin III in the body wall of the dark co10ured Arenicola and Amphitrite than in the lighter, pink specimens: the more darkly pigmented Asterias contained more protoporphyrin IX than the paler animals (Kennedy & Vevers, 1953) although protoporphyrin is not noteworthy for its photosensitizing action. Fischer & Zerweck (1924) have shown in mammals that photosensitivity to u.v.…”
Section: Discussionmentioning
confidence: 91%
“…Kench, Langley & Wilkinson (1953) found that extracts of stools of a porphyria patient, when chromatographed on paper, gave the whole gamut of porphyrins from 8-carboxyl down to 2-carboxyl. In molluscs, if free porphyrin is present it is uroporphyrin I which occurs (Kennedy & Vevers, 1954;Kennedy, 1958). In molluscs which have a shell the porphyrin is laid down in the shell, very often in a definite pattern, and in those molluscs which are without shells or have very reduced shells, such as the tectibranchs and land slugs, if uroporphyrin I is present it occurs in the integument.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fox, 1953;Vevers, 1952). In M. glacialis previous work has suggested the presence of carotenes and xanthophylls (Lonnberg, 1933;Lonnberg & Hellstrom, 1931) and whole extracts of the integument have yielded no evidence of porphyrins, despite the occurrence of protoporphyrin in the integument of the related Asterias rubens (Kennedy & Vevers, 1953).…”
Section: Identification Of the Pigmentsmentioning
confidence: 99%